Wall and floor tiling Part 4. Code of practice for ceramic tiling and mosaics in specific conditions (BSI, 1986)
Tiling, Flooring tiles, Wall tiles, Tiles, Mosaics, Ceramics, Construction operations, Grouting, Installation, Environment (working), Corrosion environments, Adhesives, Mortars, Chemical-resistance tests, Cement mortar, Swimming pools, Clean rooms, Tanks (containers), Reservoirs, Movement joints, Sealing materials, Loading, Antistatic materials, Electrical testing, Resistance measurement